2019
DOI: 10.1080/22221751.2019.1625287
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a Candida auris intra-articular infection

Abstract: A 78-year-old woman with a long-term ankle spacer with antibacterials developed an intra-articular Candida auris infection. Treatment with systemic antifungal therapy plus an amphotericin B moulded cement spacer was successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Like other Candida spp., C. auris forms biofilms on artificial surfaces and this mode of growth is presumably involved in catheter colonization by C. auris [2, 7••, 8•, 9•, 10, 11••, 12, 20, 21]. In addition, C. auris has been implicated in other device-associated infections, including central nervous system infection in the setting of neurosurgical device placement and prosthetic joint infection [22,23]. Biofilm formation is similarly anticipated to be involved in C. auris infection involving these and other medical devices [21,24].…”
Section: What Is the Clinical Presentation Of C Auris Infection?mentioning
confidence: 99%
“…Like other Candida spp., C. auris forms biofilms on artificial surfaces and this mode of growth is presumably involved in catheter colonization by C. auris [2, 7••, 8•, 9•, 10, 11••, 12, 20, 21]. In addition, C. auris has been implicated in other device-associated infections, including central nervous system infection in the setting of neurosurgical device placement and prosthetic joint infection [22,23]. Biofilm formation is similarly anticipated to be involved in C. auris infection involving these and other medical devices [21,24].…”
Section: What Is the Clinical Presentation Of C Auris Infection?mentioning
confidence: 99%
“…Another report from Japan described the eradication of Candida guillermondii infection in an oncology patient using the same combination [ 37 ]. Roberts et al reported a case of a patient suffering from C. auris intra-articular infection successfully treated with amphotericin-impregnated spacer in addition to systemic fluconazole or micafungin [ 38 ]. Apart from these case reports, there is limited evidence on this issue, and the combined therapy of echinocandins with amphotericin B has been used mostly in the treatment of invasive aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, it has been detected in 32 countries over six continents ( 2 ). C. auris infects various tissues and organs, including central nervous system ( 3 ), cardiovascular system ( 4 ), respiratory tract ( 5 ), bones and joints ( 6 ), and possesses the potential to cause nosocomial infections ( 7 ). The diagnosis of C. auris is difficult due to non-availability of specific laboratory techniques which could rapidly and accurately detect it in clinical samples.…”
Section: Introductionmentioning
confidence: 99%